Financial Sector Reforms and Monetary Policy. (IMF Working Papers; Working Paper ;, 1991)
In recent years a number of countries have undertaken far-reaching reforms of their financial sectors. Generally speaking, financial sector reforms aim at achieving greater flexibility of interest rates, an enhanced role for market forces in credit allocation, increased independence for the central bank, and a deepening of money and securities markets. Such reforms, and the developments that follow, have important implications for the design and conduct of monetary policy. This paper provides an overview of the linkages between financial sector reforms and the monetary policy framework, focusing in particular on the objectives, instruments, and operating procedures of monetary policy.